Applying cognitive science to digital human modelling for user centred design. (1st January 2012) - Thorvald, Peter; Högberg, Dan; Case, Keith
To build software which, at the press of a button, can tell you what cognition-related hazards there are within an environment or a task, is probably well into the future if it is possible at all. However, incorporating existing tools such as task analysis tools, interface design guidelines and information about general cognitive limitations in humans, could allow for greater evaluative options for cognitive ergonomics. The paper discusses previous approaches to the subject and suggests adding design and evaluative guiding in digital human modelling that will help a user with little or no knowledge of cognitive science to design and evaluate a human-product interaction scenario.